Fahr's Disease: A Very Rare Cause of Epilepsy - Hoque, MA; Siddiqui, MR; Arafat, Y; Khan, SU; Rahman, KM; Mondol, BA; Mohammad, QD (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jan;19(1):127-129 The abstract of this article is available on the PubMed website